Evaluation of Recombinant Foot-and-Mouth Disease SAT2 Vaccine Strain in Terms of Antigen Productivity, Virus Inactivation Kinetics, and Immunogenicity in Pigs for Domestic Antigen Bank - Jae Young Kim; Sun Young Park; Gyeongmin Lee; Mijung Kwon; Jong Sook Jin; Jong-Hyeon Park; Young-Joon Ko (Vaccines, 2025)
Background: Since the massive outbreak of foot-and-mouth disease (FMD) in South Korea in 2010–2011, cloven-hoofed livestock have been immunized with serotype O and A vaccines across the country. Other serotypes of FMD vaccines were stockpiled in overseas FMD vaccine factories as antigen banks. Once a manufacturing facility has been established in South Korea, the overseas antigen banks will be replaced by domestic one. Therefore, this study aimed to evaluate the commercial potential of the previously developed SAT2 vaccine candidate (SAT2 ZIM-R). Methods: The optimal condition was determined at various virus concentrations, infection times, and pH levels, resulting in 0.01 MOI for SAT2 ZIM-R for 24 h infection at a pH of 7.5. Results: When the SAT2 ZIM-R virus was produced in flasks from 40 to 1000 mL in fivefold increments, all scales of production yielded > 7.0 µg/mL of antigens. Using a bioreactor, 5.6 µg/mL of antigens was recovered from a 1 L viral culture. The optimal conditions of viral inactivation kinetics were determined to be 1 mM of binary ethyleneimine (BEI) treatment at 26 °C for 24 h, with approximately 91% of the antigen being retained after virus inactivation. When the SAT2 ZIM-R experimental vaccine was administered twice to pigs, the neutralizing antibody titer increased approximately 500-fold after booster immunization. Conclusions: To the best of our knowledge, this is the first study to evaluate the antigen productivity, viral inactivation kinetics, and immunogenicity of the SAT vaccine strain in pigs. In the future, the SAT2 ZIM-R vaccine may be a useful candidate vaccine for a domestic antigen bank.